(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Keeping plants healthy and prosperous requires the best possible growing environment. But staying on top of all environmental changes and equipment statuses or failures can be a challenge. Green house temperature should not go below a certain degree, High humidity can result to crop transpiration, condensation of water vapor on various greenhouse surfaces, and water evaporation from the humid soil. Maintaining a controlled temperature within a greenhouse environment is crucial. Temperature fluctuations can damage or kill your plants in only a few hours